Notes on the Diurnal Activity of the Enggano Flying Fox Pteropus hypomelanus enganus (Chiroptera: Pteropodidae): The Enggano Flying Fox Pteropus hypomelanus enganus - Iqbal, Muhammad; Kuswanto, Adi; Susatya, Agus (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2024)
Enggano Island Flying Fox Pteropus hypomelanus enganus is an endemic subspecies of bats from Enggano Island, Sumatra, Indonesia. During a field visit to Enggano Island in 2020 and 2021, P. hypomelanus enganus was observed always active during daylight, including in flight, looking for food, puffing and cleaning the hair. Here, we report the diurnal activities of P. hypomelanus enganus that represent first report behavior for this taxa.